Hubungan Pengendalian Ukuran Kinerja dan Kinerja Manajerial Dengan Peran Keadilan Sebagai Mediasi: Pendekatan Kerangka Konseptual - Lubis, Citra Windi; Lubis, Nurul Izzah; Utami, Anggita Atia (DAS Institute, 2024)
The performance measurement system influences the behavior of managers towards the improvement of their performance through performance appraisal in the performance evaluation process. To be an effective control mechanism, a performance measurement system must have the ability to influence managers' behavior towards desired organizational goals, which is in line with the main principles of a management control system. However, the performance measures used in the performance evaluation process must be considered fair by the manager to achieve the manager's intended behavior. The purpose of this study is to examine the effect of controlling objective performance measures on distributive and procedural justice. The proposed framework suggests that controlling objective performance measures is positively related to managers' perceptions of distributive fairness and procedural fairness. The data used is a type of secondary data sourced from the results of previous research that has been published in the form of scientific articles, literature books and official websites related to research related to performance measurement systems, managerial performance, and fairness. The results of this study reinforce the acceptance of the principle of control and its relevance in increasing managers' perceptions of fairness and in turn managerial performance with managers' cognitive perceptions of fairness further showing a positive effect on managerial performance. The results of the study also strengthen the basic premise of social exchange theory by illustrating how managers' perceptions of the fairness of their treatment, in this study, the fairness of the performance appraisal system, are reciprocated with a fairer performance appraisal system so as to produce better performance